Digital and Mobile Applications for Autism Inclusion - Moraiti, Ioanna; Fotoglou, Anestis; Drigas, Athanasios (International Journal of Online and Biomedical Engineering (iJOE), 2023)
The purpose of this research analysis is to identify the contribution of online applications to the integration of autistic individuals in typical educational contexts. The difficulties faced by both autistic people and teachers are analyzed. These difficulties are calls to improve the technology that has been introduced into the daily life of children and adults with autism. As people are becoming familiar with technology by a very young age, inexpensive applications can be used through devices such as mobiles/tablets. These applications have the power to strengthen areas in which autistic individuals fall behind. The research articles we have studied present data over the last decade, and their results are applicable to a large portion of the autistic population. Data highlighted in current analysis may be useful for improving web applications targeting autistic individuals and their families.